Vaginal Secretions Epithelial Cells and Bacteria Recognition Based on Computer Vision. (2nd December 2020) - Guo, Shaozhi; Guan, Haoyuan; Li, Jianzhong; Liao, Yonghua; Zhang, Weiwen; Chen, Shengqiang
Abstract : The examination of vaginal secretions epithelial is of great importance to female reproductive health. The results of manual detection will be affected by subjective judgment and fatigue. In this paper, an identification method based on computer vision is proposed to identify vaginal secretions epithelial cells and some bacteria. The experimental results demonstrate that the method can significantly distinguish the vaginal secretions epithelial cells from the bacteria and virus.